2007
DOI: 10.1037/0012-1649.43.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescents' and adolescents' online communication and their closeness to friends.

Abstract: The 1st goal of this study was to investigate how online communication is related to the closeness of existing friendships. Drawing from a sample of 794 preadolescents and adolescents, the authors found that online communication was positively related to the closeness of friendships. However, this effect held only for respondents who primarily communicated online with existing friends and not for those who mainly talked with strangers. The 2nd goal was to refine 2 opposing hypotheses, the rich-get-richer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
466
6
18

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 664 publications
(543 citation statements)
references
References 53 publications
39
466
6
18
Order By: Relevance
“…The alone, depressive, and anxious individuals were found to feel themselves less bounded in Internet, which they mainly use for emotional support, meeting with new people, and communicating with others. Moreover, these individuals generally prefer online communication and find the Internet communication to be sincerer and more supportive (Valkenburg and Peter, 2007). In this study, the findings differing from those of others were obtained.…”
Section: Discussion and Interpretation On If There Is Significant Difcontrasting
confidence: 70%
See 1 more Smart Citation
“…The alone, depressive, and anxious individuals were found to feel themselves less bounded in Internet, which they mainly use for emotional support, meeting with new people, and communicating with others. Moreover, these individuals generally prefer online communication and find the Internet communication to be sincerer and more supportive (Valkenburg and Peter, 2007). In this study, the findings differing from those of others were obtained.…”
Section: Discussion and Interpretation On If There Is Significant Difcontrasting
confidence: 70%
“…Most of the adolescents use the Internet for communicating with their friends (Gross, 2004). Young individuals use Internet also for communicating with strangers (Subrahmanyam and Greenfield, 2008;Valkenburg and Peter, 2007). Establishing with strangers may allow the adolescent to experience the sense of belonging.…”
Section: Discussion and Interpretation On If There Is Significant Difmentioning
confidence: 99%
“…Yet again, the potential anonymity of the Internet could make it an ideal venue for aggressive behaviors; young people could engage in relational aggression toward specific peers with little worry that they will be caught and somehow punished for their behavior. Valkenburg and Peter ( 2007 ) attempted to address some of these concerns in a survey of how a sample of Dutch youth aged 10 -16 used the Internet. They found an association between Internet use and closeness to peers.…”
Section: New Social Contexts For Peer Interaction: Internet Studiesmentioning
confidence: 99%
“…Those who played games had higher levels of self-esteem, lower levels of substance use, were more involved with school, and had closer family relationships than those who did not play games. In a study conducted on Dutch youth (Valkenburg, & Peter, 2007), online communication was positively associated with reported closeness of friendships. Similarly, Ohannessian (2009) found that media use (playing video games and watching television) served as a protective factor for at-risk youth, decreasing levels of anxiety.…”
Section: Media Use and Youth Adjustmentmentioning
confidence: 99%